Manajemen Risiko dalam Transaksi Gadai Sepeda Motor di Kelurahan Pancor Lombok Timur - Sri nirwana Nana Sarowati zikri (MANAZHIM, 2020)
This study aims to find out how risk management will be faced by the public in conducting motorcycle pawn transactions. This research uses a qualitative research approach. People in Indonesia are already familiar with the word pawn, especially in the community in the Pancor Village, East Lombok Regency, which often occurs, namely motorcycle pawn transactions. This happens when someone needs funds in an urgent and fast condition, while the person concerned does not have cash or savings funds, then third-party funding becomes an alternative solution. Based on the results of this study, people who conduct transactions, especially those who receive pawning, will carry out risk management because they are more likely to have risks. . Whereas the party giving the pawn doesn't know how much risk is being faced by the party receiving the pawn. In connection with this, I as a researcher hope that the party providing the pawn in order to further minimize the risk to the party receiving the pawn so that the party receiving the pawn has no difficulty in managing the risk.